Customer Satisfaction Analysis Using the C4.5 Algorithm at Askara Minimarket - Toto.Hermanto, Toto.Hermanto (Universitas Utpadaka Swastika, 2024)
Customer satisfaction is one way to improve the quality of service in a company, service satisfaction is also a factor in the company's development. If the company does not have quality service to the company, the company will not be able to develop and compete with other companies. The relationship between the company and consumers must run well, before employees enter the shop area, employees must be trained first. After the consumer has finished shopping, the consumer must choose whether he is satisfied or dissatisfied in the application, the results of the consumer's satisfaction and dissatisfaction will be entered into the data, this data will later be processed into Data Mining. The C45 algorithm is a data classification algorithm using a decision tree technique that is well known and preferred because it has advantages